The Measuring of Quality Services on Pasyandu Desa as The Effort to Enhance Mother and Children's Health Degree - Arif Julianto Sri Nugroho; Abdul Haris; Sumargana; Endang Eko Djati Setiawati; Sukasih Ratna Widayanti; Dandang Setyawanti (LPPM Universitas Duta Bangsa Surakarta, 2019)
The state health burden comes from the high population growth, infectious diseases, non-communicable diseases, and the higher mental health disorder. In a long period of time, this will undermine the nation’s productivity level and the economy in a country. The effort to promote the population services, health, and disease prevention need to be taken seriously. Most morbidity, mortality, population explosion, and disability as the disease effect can be prevented through promotive and preventive efforts. However, the efforts to enhance public health quality in primary service level are currently not optimal. The loose health promotion and disease prevention result the high number of morbidity and mortality. In the quarter IV 2017 there were 3.597 mothers’ died during childbirth and 22.327 infants’ death. The prevalence of the stunting toddlers or short stature was 27.6 percent, 3.4 percent of children under five were malnourished, and 14.4 percent of children under five were less malnourished [1]. This study is based on the consideration that it is necessary to conduct evaluation research on the quality services of Posyandu Desa through the Servqual model test, the importance of continuous research, and the consistency of the previous researcher. In particular, this study aims to determine the gap value and the efforts to close the biggest gap through Sevqual test. The population in this study are housewives who have children under five as the receiver of Posyandu Desa services. This study uses purposive sampling of 60 respondents in the village area of Klaten Regency. The attributes in the quality service questionnaire include tangibles, reliability, responsiveness, assurance, and empathy [2]. Quantitative tests to be conducted include the item validity test and Servqual Analysis confirmation test. From the result, it is obtained that there is still negative value with the largest negative value on the tangible dimension. The improvement efforts must be continued with emphasis on improving the value which have the largest negative dimension to enhance the quality service of Posyandu KB in the community